MANAGERIAL STRATEGY IN BALANCING TECHNOLOGY ADOPTION, LEGAL COMPLIANCE, AND HUMAN RESOURCE WELL-BEING - Freddy Damara; Nurul Hidayati; Arief Nur Adianto; Anna Yuliatin; Rakesh Sitepu (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The wave of digital disruption that has hit Indonesia has created a fundamental paradox in organizational governance. On the one hand, technology offers operational efficiency and market expansion through fintech and artificial intelligence (Artificial Intelligence). However, on the other hand, this acceleration triggers new vulnerabilities in the form of psychological pressure on employees, customer data security risks, and ethical dilemmas in trust-based industries such as Islamic banking and the media. This article aims to formulate a comprehensive management strategy capable of navigating such complexities. Through the Systematic Literature Review (SLR) approach to empirical case studies for the period 2020-2025, this study found that the success of digital transformation is not solely determined by IT infrastructure, but by human capital resilience and regulatory compliance. The study's findings show that organizations must implement an empathetic leadership model to mitigate technostress, strengthen consumer protection legal architectures, and maintain the value of humanism in automation services. The managerial implications of this study suggest the need for a shift in focus from simply "digitizing processes" to "cultural transformation" that is sustainable.